Chip-scale optical frequency comb sources for terabit communications - Marin-Palomo, Pablo (von Karlsruhe Series in Photonics & Communications, 2022)
To keep up with the ever-increasing data transmission speed needs, data center interconnects are scaling up to provide multi-Tbit/s connectivity. These links require a high number of WDM channels, while the associated transceivers should be compact and energy efficient. Scaling the number of channels, however, is still limited by the lack of adequate optical sources. In this book, we investigate novel chip-scale frequency comb generators as multi-wavelength light sources for Tbit/s WDM links.